2020
DOI: 10.3390/app10030963
|View full text |Cite
|
Sign up to set email alerts
|

Serious Game Platform with Haptic Feedback and EMG Monitoring for Upper Limb Rehabilitation and Smoothness Quantification on Spinal Cord Injury Patients

Abstract: Cervical Spinal Cord injury (SCI) is a neurological disease that produces, as a consequence, impairments of the upper limb function. This paper illustrates a virtual reality platform based on three serious games for upper limb rehabilitation with electromyography monitoring, providing force feedback to the patient. In the rehabilitation process proposed, haptic feedback was provided to the patients to strength the arm muscles by means of the Novint Falcon device. This end-effector device was used to manipulate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Although VR-based systems could provide many advantages in neurorehabilitation, such as offering precise measurement, increasing motivation, providing direct feedback and safe environments [ 12 , 40 ], the results obtained in our study revealed that VR interventions might not be more effective than CPT in improving functional performance in patients with SCI. Moreover, the statistical analysis showed favorable results of CPT on the functional independence measured by the FIM scale.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Although VR-based systems could provide many advantages in neurorehabilitation, such as offering precise measurement, increasing motivation, providing direct feedback and safe environments [ 12 , 40 ], the results obtained in our study revealed that VR interventions might not be more effective than CPT in improving functional performance in patients with SCI. Moreover, the statistical analysis showed favorable results of CPT on the functional independence measured by the FIM scale.…”
Section: Discussionmentioning
confidence: 73%
“…Due to the rise of this novel technology application in clinical neurorehabilitation in recent years [ 12 ], a large number of studies on the use of VR interventions have been conducted in different neurologic disorders, such as: cerebral palsy [ 13 , 14 ], multiple sclerosis [ 15 , 16 , 17 ], stroke [ 18 , 19 , 20 , 21 ], Parkinson’s disease [ 22 , 23 ]. However, the ratio of functional recovery is different for each disease, so the desired effects provided by VR interventions could be different.…”
Section: Introductionmentioning
confidence: 99%
“…VR has been used in clinical settings to treat a range of cognitive, emotional and motor problems in various psychological and psychiatric disorders [9,[11][12][13][14][15][16]. Many studies have shown that the VR-based therapy is as effective as their in-vivo (traditional) counterpart [13,17,18].…”
Section: Related Workmentioning
confidence: 99%
“…The arousal is again a max function of the current values of stress, fear and the new candidate values of arousal. The candidate new arousal is based on the preference towards music, the intensity of natural light and the intensity of artificial light as defined in Equation (11). In short, arousal will only increase when fear or stress increases, and it will only decrease when the music is optimal and/or the environment is bright.…”
Section: A X Range a X F A X Sp A X S Ax Ap A X A A X Rp A X R A Xmentioning
confidence: 99%
“…The secondary parenchymal damage is of prolonged nature, based on which candidate treatment modalities have been developed [13][14][15][16]. The severity of the initial TSCI may serve as an indicator of the characteristics and degree of the secondary response; it may also be used to determine optimal treatment modalities [17,18].…”
Section: Introductionmentioning
confidence: 99%